The Effect of Coloured Puzzle Media on The Ability to Recognize Geometrical Shapes of Kindergarten Students - Shafa Latifah; Nurhafizah Nurhafizah (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
This research was based on finding the weakness of children’s ability to mention geometric shapes, which was caused not yet optimal, and the learning media provided was less attractive. This study looked at the effect of color puzzle media in increasing children's ability to recognize geometric shapes in kindergarten. Pre-experimental quantitative method or quasi-experimental was used in this research. The research sample consisted of 15 children without a control class. The sampling technique is a purposive sampling technique. The research data were analyzed using the SPSS (statistical product and service solution) application type 17 with the t-test hypothesis test. The results of this study positively impact learning outcomes to recognize geometric shapes in kindergarten because of an increased children's ability to identify through color puzzle media. The results obtained sig value 0.000 and t-count (40.905) t-table (2.145). It is stated that hypothesis Ha was accepted, and hypothesis Ho was rejected. So the color puzzle media has an influence on recognizing geometric shapes in children in kindergarten and obtained significant results with a change of fifty point three percent (54.3%). So in this study, it is said that colored puzzle media increases children's ability to recognize geometric shapes in kindergarten. With the hope that this learning media is used as a tool for recognizing geometric shapes in children, making it easier for children to learn.